Complexation Study of N-Phenylaza-15-Crown-5 with Cd2+ Cation in Binary Mixed Non-aqueous Solvents - Hossein Rounaghi, Gholam; Tarahomi, Somayeh; Karimi, Massoumeh (Asian Journal of Chemistry, 2012)
The complexation reaction of N-phenylaza-15-crown-5 (PhA15C5) with Cd2+ cation was studied in acetonitrile-methanol, acetonitrile-butanol, acetonitrile-ethylacetate, acetonitrile-nitromethane and methanol-propylencarbonate binary solvent solutions, at different temperatures by conductometric method. The stability constant of the resulting 1:1 complex at each temperature was determined using a computer fitting conductance-mole ratio data. A non-linear relationship was observed for changes of log Kf of (PhA15C5.Cd)2+ complex versus the composition of the binary mixed solvents. The corresponding standard thermodynamic parameters (DHºc, DSºc) were obtained from temperature dependence of the stability constant. The results show that the complexation reaction is enthalpy destabilized but entropy stabilized.